Influence of Microstructural Characteristics on Wear and Corrosion Behaviour of Si3N4-Reinforced Al2219 Composites. (20th February 2023) - Manjunatha, C. J.; Prasad, C. Durga; Hanumanthappa, Harish; Kannan, A. Rajesh; Mohan, Dhanesh G.; Shanmugam, Bharath Kumar; Venkategowda, C.
Abstract : The fabrication of the Al2219 + Si3 N4 composites was done by means of stir casting process. The specimen was subjected to microstructural studies. The density of Si3 N4 employed in the fabrication of the composites has been evaluated. Generally, the density of the composites increases as the weight percent of Si3 N4 increases. TGA and DTA were performed at temperatures ranging from 30°C to 800°C, with some mass loss noted as well as the thermal stability of an AA2219 matrix improved. Under various parameters of applied load, operating duration, and speed, the wear behaviour of the produced aluminium matrix composite (AMC) was examined. Corrosion behaviour was examined using potentiodynamic polarization curve data, and it was discovered that the rate of corrosion decreases with increasing Si3 N4 content, adding to the AA2219 matrix. The research work is intended to produce a totally new composite material with various compositions of reinforcement and to investigate their mechanical properties and a result of simulation.